Assessing the Quality of Life of Pregnant Women Using a New Pregnancy Belt: A Randomized Controlled Trial (RCT) Study - Zhaleh Heydari; Mohammad Ali Mardani; Akbar Biglarian; Maryam Shokrpour; Gholamreza Aminian (Shiraz University of Medical Sciences, 2023)
Background: Quality of life (QOL) is a multidimensional concept encompassing physical, mental, emotional, and social functions. Lumbar pain (LP) experienced during pregnancy can have a negative impact on QOL, but the use of pregnancy belts has been known to improve it. Presently, these belts' most common design pattern involves an adjustable one-piece panel at the pelvic girdle (PG) but does not support the lumbar region. However, the new pregnancy belt evaluated in this study is designed to support the lumbar and pelvic girdles simultaneously. The primary objective of this study is to assess the QOL of pregnant females experiencing lumbar pain while using the new pregnancy belt compared to the current belt (CB).Methods:  In this randomized controlled trial study, a total of 48 pregnant females experiencing pregnancy-related lumbar pain (LP) participated. They were divided into three groups: the CB, new belt, and control groups. At the beginning of the study and after three weeks, all groups completed a demographic questionnaire and a Quality of Life (QOL) questionnaire using the SF36 tool.Results: After three weeks, all eight health concepts of the SF36 questionnaire showed improvement in both the CB and new belt user groups. However, in the control group, there was a decrease in these health concepts during the same period. A significant difference was observed in the physical and mental health scales when comparing the new belt group to the CB group. However, the two variables had no significant difference, with p-values of 1.00 and 0.15, respectively.Conclusion: Based on the study's findings, it can be inferred that the new pregnancy belt has a more significant impact on enhancing the Quality of Life (QOL) of pregnant females compared to the CB (current belt).